Perfil clínico y funcional de pacientes con diagnóstico de ACv, atendidos durante año 2009 en Servicio de Rehabilitación, Hospital Militar de Santiago - Prado P., Lorena; Ritter A., Paola; Ojeda M., Mario; Mora C., Carolina (Revista Hospital Clínico Universidad de Chile, 2013)
The early rehabilitation is recognized as a key factor in the prognosis of patients with stroke, but the way it should be done is not clarified. National and international guidelines have been developed that establish certain standards, which are not always able to be implemented in the reality of each center. This descriptive study presents the characteristics of a group of hospitalized patients who receive rehabilitation unorganized during the acute phase of stroke and their clinical / functional within two years. The epidemiological and clinical characteristics generally were similar to those reported in the literature. In most patients are not recorded or test scales to quantify the shortfall. It is observed that the majority receive early attention by physiotherapist and occupational therapist. Assessments for medical rehabilitation and multidisciplinary team meeting are less common and more complex patients, but in this group of patients at two years have seen a decrease in the number of deficiencies and complications. Multiple factors may be involved in the functional outcome of patients, which needs to be studied in future. Given that there is underreporting of clinical evaluations of importance to develop individualized rehabilitation plans for each patient, we propose a registration pattern with which we consider elevant.